Synthesis and temperature-induced self-assembly of a positively charged symmetrical pentablock terpolymer in aqueous solutions. (December 2017) - Dashtimoghadam, Erfan; Salimi-Kenari, Hamed; Forooqi Motlaq, Vahid; Hasani-Sadrabadi, Mohammad Mahdi; Mirzadeh, Hamid; Zhu, Kaizheng; Knudsen, Kenneth D.; Nyström, Bo
Graphical abstract: Highlights: Self-assembling of a cationic temperature sensitive pentablock copolymer. Temperature-induced formation of micellar and intermicellar structures. Building-up and breaking-up of interchain complexes under the influence of shear flow. Abstract: A novel linear cationic ABCBA pentablock terpolymer composed of a positively charged poly (3-acrylamidopropyl) trimethyl ammonium chloride)) (PAMPTMA (+)) block at both ends and two thermoresponsive poly ( N -isopropylacrylamide) (PNIPAAM) blocks separated by a hydrophilic poly(ethylene glycol) (PEG) block was synthesized via a "one-pot" atom transfer radical polymerization procedure (ATRP). The chemical composition of the pentablock terpolymer was confirmed by nuclear magnetic resonance (NMR) and asymmetric flow field-flow fractionation (AFFFF). Depending on the polymer concentration in aqueous solution, this terpolymer forms unimers and self-assembled structures at elevated temperatures. The effect of concentration and temperature-induced self-assembling behavior of the pentablock terpolymer in aqueous solution was examined by using turbidimetry, shear viscosity, rheo-small angle light scattering (rheo-SALS), dynamic light scattering (DLS), and small angle neutron scattering (SANS). The turbidity measurements demonstrated that the formation of intermicellar structures and compaction of the complexes are function of both polymer concentration and temperature. The viscosity and rheo-SALS experiments elucidated the intricate interplay between building-up and breaking-up of interchain complexes under the influence of shear flow. The DLS experiments show the coexistence of small entities and interchain complexes at low temperatures and the evolution of large intermicellar structures at higher temperatures. At the highest temperatures, compaction of the complexes occurred. The results from SANS revealed significant temperature-induced changes of the copolymer structure on a semi-local dimensional scale.